HUBUNGAN PENGETAHUAN IBU TERHADAP TINGKAT PARTISIPASI MASYARAKAT (D/S) DI POSYANDU DESA BAYA BETUNG WILAYAH KERJA PUSKESMAS PANDAN KECAMATAN SUNGAI TEBELIAN KABUPATEN SINTANG - Ellys Nurmaida Silalahi; Didik Hariyadi (Poltekkes Kemenkes Pontianak, 2018)
Posyandu is one of the Efforts the health community’s Power Stems (UKBM) which is managed and organized from, by, for and with communities in implementing health development. UKBM can empower communities and provide convenience to the public in obtaining basic health services to accelerate the decline in the death rate of mothers and babies. This research aims to know the mother’s knowledge, the relationship with the level of participation of the community in the village of Posyandu Baya Betung working area Pandan River Subdistrict health centers Tebelian Regency Sintang. This type of research is observational design with Cross Sectional (Pieces of latitude). The research was carried out in the village of Baya Betung working area Pandan Tebelian River Subdistrict health centers on December 29, s/d January 3, 2015. The respondents in this study were the mother of a toddler. How to use data collection interviews using questionnaire instruments. The results showed no relationship between mother’s knowledge (p = 0.05) with the level of participation of the community in the village of Baya Betung working area Pandan River Subdistrict health centers Tebelian Regency Sintang. It is recommended to provide guidance about the benefits to mother and toddler posyandu layout posyandu is close to the community.